1998
DOI: 10.1002/(sici)1097-4644(19980301)68:3<287::aid-jcb1>3.3.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of in vitro mineralization from rabbit aorta and their role in biomineralization

Abstract: Mineralization of aorta is known to occur late in life and appears to be a pathological phenomenon. In vitro studies revealed that the matrix prepared from the thoracic aorta pieces after their extraction with 3% Na2HPO4 and 0.1 mM CaCl2 were mineralized under physiological conditions of temperature, pH, and ionic strength of the media to form matrix-bound mineral phase resembling hydroxyapatite in nature. However, the matrix identically prepared from the unextracted rabbits aortae failed to mineralize under i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
7
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…and high molecular weight substances (e.g., polypeptides, proteins, glycoproteins, etc. ), which by acting as inhibitors of mineral phase formation may play an important role in the etiology of urolithiasis [Howard and Thomas, 1958; Grover et al, 1994; Tandon et al, 1997, 1998; Aggarwal et al, 2000].…”
mentioning
confidence: 99%
“…and high molecular weight substances (e.g., polypeptides, proteins, glycoproteins, etc. ), which by acting as inhibitors of mineral phase formation may play an important role in the etiology of urolithiasis [Howard and Thomas, 1958; Grover et al, 1994; Tandon et al, 1997, 1998; Aggarwal et al, 2000].…”
mentioning
confidence: 99%
“…This theory is supported by data showing that tendon extraction with 3% Na 2 HPO 4 leads to a quick mineralization and re‐adding the extract significantly inhibits the rates of calcium and phosphate uptake from the soluble phase . However, a recent study showed that when the Na 2 HPO 4 ‐extracted tendon was incubated in a solution containing both calcium and phosphate, the mineralization process only lasted for several hours . A decline in free calcium occurred quickly because of the spontaneous formation of apatite crystals in solution containing increased levels of calcium and phosphate .…”
mentioning
confidence: 89%
“…However, it usually does not occur in humans, unless subjected to a pathological change resulting from injury, degenerative disorders, or tendinitis, which alter the normal tendon function. To prevent or treat this problem, many studies were conducted to explore the mechanism of mineralization, some of which indicated that a still unidentified macromolecular inhibitor plays an important role to preclude tendon or other soft tissue calcification . This theory is supported by data showing that tendon extraction with 3% Na 2 HPO 4 leads to a quick mineralization and re‐adding the extract significantly inhibits the rates of calcium and phosphate uptake from the soluble phase .…”
mentioning
confidence: 99%
See 2 more Smart Citations